Liberalism and its discontents - Brinkley, Alan (ACLS Humanities E-Book (Series), 1998)
How did liberalism, the great political tradition that from the New Deal to the 1960s seemed to dominate American politics, fall from favor so far and so fast? In this history of liberalism since the 1930s, a distinguished historian offers an eloquent account of post-war liberalism, where it came from, where it has gone, and why. The book supplies a crucial chapter in the history of twentieth-century American politics as well as valuable and clear perspective on the state of our nation's politics today.